PENGENDALIAN KECEPATAN ANGIN UNTUK KENDALI SUHU PADA PETERNAKAN AYAM DI PT VSA - Sukarno, Setyawan Ajie; Satyaka, Adhit; Sopana, Dodi; Ichsan M., Isbail; Hidayatullah, Nur Iqbal (Politeknik Negeri Sriwijaya, Indonesia, 2024)
In this era, the technology development is increasing rapidly. Especially in the field of control systems. One of the development is a controlling method known as fuzzy logic control. This method applies a simple system with reliable output. Control systems applied in various fields, including in livestock industry. In livestock industry, one of the largest end product is eggs. Eggs are a commodity that cannot be separated from everyday life. To get high quality eggs, laying hens in their cages must be kept in certain condition so they are relaxed and comfortable. One of the influencing factors is the temperature in the cage. High temperature in the chicken coop can make the chickens stressed out and uncomfortable. Based on this, a control system is made to regulate the level of temperature and air circulation in the chicken coop. The system uses temperature, humidity and wind speed sensors which control a fan motor speed. This system is built using Controllino and Labview as the main controls which implement a fuzzy control system. The results of this study are the level of accuracy of the application of the fuzzy method in controlling the temperature of the chicken coop.